CONNECTED SPEECH PROCESSES IN DIFFERENT STYLES OF ENGLISH - Fayzulloyeva Zilola Zafarovna,; Ramozonova Dilnura, (TADQIQOTLAR, 2026)
Annotation    This  article  will  provide  information  about  connected  speech  that  differs between formal and informal styles. Casual, spontaneous conversations often show numerous reductions and elisions, whereas formal or prepared speech maintains clearer articulation and controlled rhythm. Research by Gillian Brown and Rodney Huddleston demonstrates  that  such  phonetic  differences  are  socially  meaningful,  signaling formality,  emphasis,  emotion,  and  interpersonal  interaction.  In  addition,  connected speech  contributes  to  expressing  social  identity,  regional  affiliation,  and  group membership.